Kidney Disease in Human Immunodeficiency Virus-seropositive Patients: Absence of Human Immunodeficiency Virus-associated Nephropathy was a Characteristic Feature - Prakash, J. (Indian J Nephrol, 2017)
Human immunodeficiency virus (HIV) infection can cause a broad spectrum of renal diseases. However, there is paucity of Indian data on the patterns of renal lesions in HIV-seropositive patients. The aim of the present study was to delineate the spectrum of renal lesions in HIV/acquired immunodeficiency syndrome patients. In this prospective study, all HIV-positive patients of both genders aged >18 years were screened for renal disease. Patients with proteinuria of more than 1 g/24 h were subjected to renal biopsy. A total of 293 HIV-positive patients were screened; of these, 136 (46.4%) patients found to have renal involvement. Dipstick-positive proteinuria of 1+ or more was observed in 112 (38.2%) patients, and 16 (14.2%) patients had proteinuria of more than 1 g/24 h. Renal biopsy in 14 cases revealed glomerulonephritis (GN) in 12 (85.7%) (isolated GN in 4 [28.5%] and GN mixed with chronic TIN in 8 [57.1%]) patients. These include mesangioproliferative GN in 5 (35.7%), membranoproliferative GN in 2 (14.2%), focal segmental glomerulosclerosis in 2 (14.2%), diffuse proliferative GN in 2 (14.2%), and diabetic nephropathy in 1 (7.1%) patients. Chronic interstitial nephritis was noted in 10 (71.42%) (superimposed on GN in 8 [57.1%], isolated in 2 [14.2%]) patients. Granulomatous interstitial nephritis was seen in 3 (24.1%) cases. GN and chronic interstitial nephritis were noted in 85.7% and 71.42% of patients, respectively, mostly superimposed on each other. Mesangioproliferative GN was the most common glomerular lesion, but classical HIV-associated nephropathy was not observed.